Climate Change Adaptation Strategies for Better Agricultural Productivity: A Systematic Literature Review - Khanal, Ashish; Sapkota, Chandra Kant; Adhikari, Jagadish; Sapkota, Kiran Kishor; Raut, Pappu Kumar; Bajracharya, Prajita; Bhatta, Rachana; Rai, Subhakarna; Gongba, Shimran; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2026)
Climate change poses a severe threat to global agricultural productivity, food security, and livelihoods, particularly in vulnerable developing nations. Understanding effective adaptation strategies is critical for building resilient agricultural systems. This systematic literature review synthesises evidence published between 2015 and 2025 on climate change adaptation strategies for enhancing agricultural productivity, with a focus on three themes: climate change impacts, adaptation strategies, and productivity outcomes.A systematic search was conducted with Boolean operators. The search string combined terms related to climate change, agricultural productivity, and adaptation strategies. Inclusion criteria were peer-reviewed English-language articles published from 2015 to 2025. A total of 60 articles met the inclusion criteria and were thematically synthesised. Climate change, driven primarily by anthropogenic greenhouse gas emissions, reduces crop yields, threatens livestock, and exacerbates food insecurity. However, multiple adaptation strategies demonstrate effectiveness. Precision agriculture using IoT reduced water use by 25% and increased yields by 20%. AI-driven modelling improved crop yields by 15%. Sustainable intensification lowered pesticide use by 36% and increased rice yields by 12–54%. Community-based adaptations such as crop diversification and riverbed farming proved effective in local contexts. Nevertheless, residual yield losses of approximately 8% by 2050 are projected even with adaptation. Climate change adaptation can partially offset agricultural losses, but adaptation alone is insufficient. Urgent global mitigation efforts to reduce emissions are indispensable. Tailored, context-specific strategies that integrate technology, traditional knowledge, and supportive policies offer the most promising pathway to resilience.